Exploring the effects of lysozyme dietary supplementation on laying hens: performance, egg quality, and immune response - Sindaye, Daniel; Xiao, Zaili; Wen, Chaoyu; Yang, Kang; Zhang, Limeng; Liao, Pinfeng; Zhang, Fan; Xin, Zhongquan; He, Shansong; Ye, Shibin; Guo, Dan; Hang, Suqin; et al. (Frontiers in Veterinary Science, 2023)
An experiment was conducted to evaluate the dietary supplementation with lysozyme’s impacts on laying performance, egg quality, biochemical analysis, body immunity, and intestinal morphology. A total of 720 Jingfen No. 1 laying hens (53 weeks old) were randomly assigned into 5 groups, with 6 replicates in each group and 24 hens per replicate. The basal diet was administered to the laying hens in the control group and it was supplemented with 100, 200, 300, or 400 mg/kg of lysozyme (purity of 10% and an enzyme activity of 3110 U/mg) for other groups. The preliminary observation of laying rate lasted 4 weeks and the experimental period lasted 8 weeks. The findings demonstrated that lysozyme might enhance production performance by lowering sand-shelled eggs rate (P<0.05), particularly 200 and 300 mg/kg compared to the control group. Lysozyme did not show any negative effect on egg quality or laying hen health (P>0.05). Lysozyme administration in the diet could improve intestinal morphology, immune efficiency, and nutritional digestibility in laying hens when compared to the control group (P<0.05). These observations showed that lysozyme is safe to use as a feed supplement for laying hens’ production. Dietary supplementation with 200 to 300mg/kg lysozyme should be suggested to farmers as a proper level of feed additive in laying hens breeding.